Efficacy of four irrigation needles in cleaning the apical third of root canals - Guerreiro-Tanomaru, Juliane Maria [UNESP]; Loiola, Livia Etchebehere [UNESP]; Morgental, Renata Dornelles; Leonardo, Renato de Toledo [UNESP]; Tanomaru-Filho, Mario [UNESP] (FapUNIFESP (SciELO), 2013)
This study aimed to evaluate the influence of irrigation needle gauge and design, and the final root canal diameter on the apical cleaning efficacy. Twelve human mandibular incisors were used. At different stages of root canal widening (sizes 20, 30 and 40 K-files), root canals were filled with radiopaque contrast medium. Four different needles were evaluated: 23G with side opening, 22G with apical opening, 30G with side opening and 30G with apical opening. Irrigation was carried out with 2 mL distilled water. The same tooth was radiographed with a digital system several times to assess the four types of needle in those three stages of canal widening. Pre-irrigation (canals filled with contrast) and post-irrigation (canals with remaining contrast) images were submitted to digital subtraction using the Adobe Photoshop CS4 program. Pre-irrigation (filled with contrast) and subtracted (cleaned by irrigation) areas were outlined by a trained and blinded operator using the Image Tool 3.0 software. Their ratio was calculated to express the percentage of apical cleaning in each stage of canal widening (sizes 20, 30 and 40 K-files) with each of the four needles. Data obtained were subjected to one-way ANOVA and Tukey's tests. The 30G needles with side and apical opening promoted better apical cleaning at all stages of root canal widening (p<0.05). In conclusion, smaller diameter needles were more efficacious in cleaning the apical third of the root canals, regardless of their design.
Keywords: Digital radiography; Endodontics; Root canal irrigants; Root canal preparation